Persephone's garden - Fawkes, Glynnis (Secret Acres, 2019)
"A children's song inspires a love of Greek mythology in a young girl. A young woman finds a career in archeology and illustration. A young mother sees her daughter become a woman, as her own mother's memories are lost. Persephone's Garden is a deeply personal story and an inventive study of girlhood, womanhood and motherhood, through memory, history and mythology."--Amazon.